Comparison of Anthropometric Characteristics, Body Composition Profile and Physical Fitness Parameters of Indian National Women Rugby Players According to Their Specific Playing Position - Sarkar, Surojit; Dey, Swapan Kumar (International Journal of Sport Studies for Health, 2019)
Background: Scientific researches available on anthropometric and physiological characteristics of female rugby players in India are very scanty.Objectives: The present study was aimed to evaluate and compared different anthropometric, body composition and physical fitness parameters and also to investigate whether any distinctive characteristics exist among above variables according to their specific playing position.Methods: Twenty five Indian national women rugby players (forward, n = 12, mean age = 20.9 ± 3.30 and back, n = 13, mean age = 19.7 ± 2.48) of pre-competitive phase were chosen as subject from the national coaching camp. They were evaluated for various anthropometric, body composition parameters, hemoglobin, blood glucose level and physical fitness profile by following standard procedure.Results: Forward players had significantly higher body weight, BMI, fat percentage, sum of skinfold, total body potassium, total body calcium and glycogen content as compared to the back. Whereas, players of back position had significantly higher relative muscle mass (MM/Wt.), relative body cell mass (BCM/Wt.), agility, standing broad jump, VO2max and relative peak anaerobic power than their forward counterparts. Linear regression model identified agility (β = 0.59) and sum of skinfold (β = -0.45) as significant predictor of peak anaerobic power (adjusted R2 = 0.61) of these players.Conclusions: Present study indicated the players of back position were faster, more agile and aerobically fit with having lower body weight and fat percent as compared to their forward counterparts. Whereas, principal component analysis identified BMI, sum of skinfold and agility as the main confounding variables to categorize the present rugby players between forward and back positional groups.